Computational analysis of 1,3-propanediol operon transcriptional regulators: Insights into Clostridium sp. glycerol metabolism regulation - Barragan, Carlos Eduardo; Instituto de Biotecnología Universidad Nacional de Colombia (2014)
We designed a strategy for the sequencing and bioinformatical characterization of the 1,3-propanediol operon regulator genes from the Colombian Clostridium sp. strain IBUN13A, which is taxonomically related to Clostridium butyricum. Three genes are proposed to be involved in the operon’s transcriptional activity, the dhaS and dhaA genes through a two-component system and the third gene named dhaY, which encodes a putative transcriptional regulator similar to the domains of the dhaS/A system. Phylogenetic analyses indicated that the predicted proteins had a modular structure consisting of domains homologous to different signal transduction systems, but had significant differences concerning their conserved residues, pointing to the possibility that they constitute ancestral domains. In accordance with the prediction of functions, we propose a mechanism of regulation of the proteins studied of the 1,3-propanediol operon of the native strain, as a response to the presence of glycerol in the medium, which provides valuable information on the overall regulation of the glycerol metabolism in Clostridium sp.